THEATRICAL LIFE AND REPERTOIRE OF THE MARIONETTE THEATRE OF ESTERHÁZ - Kata ASZTALOS (Studia Universitatis Babeş-Bolyai. Musica)
The marionette operas are closely connected with the Esterházy court of the 18th century as well as the work of Joseph Haydn; nevertheless they hold values for the audience of the 21st century as well. This study presents the history of marionette operas in Esterház. The focal point of the essay is an analysis of the functioning of the marionette theatre based on date, authors and works. The increasing numbers of marionette operas staged today in Hungary and the on-going explorations of the marionette theatre in Fertőd confirm the relevance of this matter. Since the genre of marionette opera lacks Hungarian academic literature, English and German publications provide the background for this study; archives, illustrated materials and musical resources of that period are further examined as well. With the use of these materials we can have an insight not only into a marionette theatre which was extraordinary in its age but an exceptional repertoire as well, for accomplished composers of the 18th century had produced works for the marionette theatre of Esterház.